Influences of thickness and geometrical change from draw forming in quasi-static axial compression simulation - Mohd Amman, Rosmia; Halim, Mohd Faizal; Dhar Malingam, Sivakumar; Abu Shah, Ismail (Praise Worthy Prize, 2016)
In the current industrial practices in the automotive field, the forming effects are neglected in the automotive crash analysis simulation. However, in reality, the forming process alters the structural behaviour of these components significantly. The objective of this paper is to present the effect of draw forming in the quasi-static axial compression analysis. In the present work, a circular cup is draw formed using Dual Phase (DP600) steel followed by a compression analysis to quantify the effects of non-uniform thickness distribution and the geometrical change on the cup. Numerical compression simulation was carried out with RADIOSS to identify these effects which were modelled using, in case A, a CAD circular cup and, in case B, a formed circular cup from draw forming. The experimental work was done to validate the forming model before compression analysis. Quasi-static axial compression simulation results revealed that the peak load and the energy absorbed for case B are lower by 26.91% and 17.84% respectively compared to case A. The compression analysis results demonstrate that the effect of non-uniform thickness distribution from draw forming process gives significant effect in the subsequent analysis. Therefore, the forming effects should be considered when conducting a crash simulation to increase the crash prediction and safety.